The Impact of Student-Oriented Worksheets for Differentiated Learning (LKPD) on Students' Physics Learning Outcomes at MAN Binjai - Putri, Najwa Aulia; Ridwan Abdullah Sani (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The study aims to determine the effect of differentiated learning using learning style-oriented Student Worksheets (LKPD) on student learning outcomes in sound wave material at MAN Binjai T.P 2022/2023. This type of research is quasi-experimental, and the research design is a Control Group Pre-Test-Post-Test Design with a population of all students of class XI MIA MAN Binjai consisting of 4 classes. The research sample was taken by two classes determined by random sampling technique, with XI MIA-3 as the experimental class, totaling 35 people who were treated with differentiated learning using learning style-oriented worksheets, and the control class XI MIA-4, totaling 35 people who were given inquiry learning treatment. The instrument used was a multiple-choice test of learning outcomes with 15 validated questions and student learning activity assessment sheets in the experimental class. The results of the data analysis obtained an increase in student learning outcomes in the experimental class of 73.71 and the control class of 65.33. In addition, the increase in student activity in each meeting was very good. After implementing differentiated learning using learning style-oriented worksheets, the results significantly affected student learning outcomes in sound waves material at MAN Binjai T.P 2022/2023.